End‐tidal capnography provides reliable ventilatory monitoring for non‐intubated patients presenting after sedative overdose to the emergency department. (26th November 2019) - Millane, Teri; Greene, Shaun; Rotella, Joe‐Anthony; Leang, Yit Hung
Abstract: Objective: To assess the ability of end‐tidal capnography to provide continuous ventilatory monitoring in sedated, non‐intubated ED patients following sedative overdose. Methods: Observational study undertaken in a tertiary hospital ED. Patient ventilation was assessed using capnography over 60 min. Results: Capnography provided uninterrupted monitoring for 99% of total study time. Capnography detected all episodes of hypoxia detected by SpO2 monitoring. Changes in capnography preceded 70% of hypoxic episodes detected by SpO2 . There were no major adverse events or incidents of device failure. Conclusion: Capnography provided reliable measurement of ventilatory function in sedated non‐intubated, poisoned ED patients.